Tourism between disputes over territory, Zapotitlán Salinas, Puebla - Zárate Hernández, Eduardo; Cortés Márquez, Nubia (Revista Mexicana de Ciencias Agrícolas, 2018)
Promoting local development through tourism is expressed in changes of use and access to the strategic resources of the territory. The emergence of new political agents seeking to assert their rights as citizens, also disputing the ground to access different types of owners who live there. Ethnography and participant observation allows getting closer to the subjects, main agents and producers, live, weave patronage or power-related relationships, building their own space of negotiations. Population practices set internally differentiated territories which emphasizes the active role of citizenship in promoting decentralization policies. Zapotitlán Salinas, is an example of assemblies and citizen territory and institutional right that overlaps with the heterogeneity of forms of local ownership. In these cases we try to show the juxtaposition of different temporal orders of new territorialities assembled from promoting local development policies such as tourism. Understand how new territorialities are assembled in a particular town offers a glimpse of how the power at the local or regional level is actually distributed.
Keywords: dispute; local development; territoriality